PROSES PERSONAL SELLING PRODUK INDUSTRI PERTANIAN PT. RUMAH BIO INDONESIA - Sarah Esther; Deavy MRY Johassan (Jurnal Komunikasi dan Bisnis, 2019)
In selling industrial products, the use of salespeople is very important. However, according to the researcher's observation, information about the salesperson's functions in selling agricultural industrial inventory products is still rarely revealed. The researcher used one of the marketing communication mixes, namely personal selling, which has an explanation of the salespersonâ€™s functions for this research. The researcher used qualitative research with descriptive type. The primary data is the results of the interview with informants. The researcher found information about the personal selling process and the salesperson's functions in selling agricultural industrial inventory products. The researcher found the core of the personal selling process at PT. Rumah Bio Indonesia is to present product knowledge and give a product testing and demonstration named â€œUji Demplotâ€, close the sales, and give the after-sales service especially in building communication and solving customerâ€™s problems. The researcher also found explanations of the salesperson's functions for the company. The first function is to create new customers, can be seen by the addition of 500 clients from 2017 to 2018. The second function is to sell more to current customers, can be seen by the sales of new products to the current customers. The third function is to provide market information for the company, the information provided by the salesperson is following the conditions in their respective regions, information is provided during meetings at the head office, in Jakarta.Â Keywords: Function of Salesperson, Industry Inventory Products, Agricultural Industry.